Perancangan Sistem Informasi Warga di Rw 01 Kelurahan Kebon Bawang Berbasis Web - Sarimole, Frencis Matheos; Surapati, Untung; Purwandono, Eddy; Karim, Lutfi; Diadi, Randitia Ridad; Syaeful, Achmad; Wibawa, Andri Putra (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Rukun Warga 01 is an area located in Kebon Bawang Village, Tanjung Priok District, Central Jakarta. Where, currently RW 01 services are still carried out conventionally, starting from population data management, administration in the form of cover letters, disseminating information from RW to each RT. Data processing is currently done by recording in the bookkeeping archive. Dissemination of information to residents still relies on information boards or through person to person, and administrative letters such as cover letters have not implemented computerized methods or are still using manuals. Knowing this, the current system is considered to be still less effective if used continuously it can make it difficult to find data, errors often occur and the distribution of information is uneven. Therefore, a website-based information system was created. To support this, the authors collect information through observation, interviews, literature study. The system development methodology used is the SDLC (System Develop life Cycles) method using the Waterfall model. This website is made with PHP programming language and MySQL as database. The results of the research This information system makes a computerized system that makes it easier for RW administrators to collect citizen data and provide information that is accurate and fast, and evenly distributed